Radio Dakwah dan Komunikasi 107,9 FM UIN Jakarta: Pengamatan Media Sebagai Industri - Ramadhan, Sendi; Nabillah, Osha; Fatwa, Bagya Husna; Anggian, Kiki Yulia; Bakti, Andi M. Faisal (Academic Journal of Da'wa and Communication, 2024)
Information technology has changed the behavior of Indonesian society a lot. This is in line with the growing public need for information. Radio is one of the mass information media that has strong penetration capabilities into the market and consumers. This research aims to analyze Radio RDK 107.9 FM as a da'wah media from a media industry perspective. The method used in this research is analytical descriptive. The subjects of this research were the production crew & administrators of Radio RDK UIN Jakarta. The object of this research is RDK Radio. The theory used by Gill Branston and Roy Stafford is that media is produced like a factory. The results of this research reveal that Radio RDK is a community radio that runs media like a factory, by paying attention to factors such as frequency, duration, timing/showing time, and the prominence of other auditive aspects. RDK Radio is a medium for preaching to its listeners. Based on these factors, good RDK Radio program packaging becomes part of the strategy for preaching via radio to achieve optimal effects among the radio-listening community.